Di Antara Tiga Launchpad : Indonesia dan Dinamika Diplomasi Antariksa dalam Geopolitik Indo-Pasifik - Deden Habibi Ali Alfathimy; Yunita Permatasari; Euis Susilawati; Dini Susanti; Shinta Rahma Diana; Joko Susanto; Aristyo R. Darmawan (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2021)
The geopolitical dynamics of the Indo-Pacific region are also influenced by the cooperation and competition between China, Japan, and India in the space realm. Indonesia, which is in the middle of this geopolitical area and has a national interest in space, is in a situation that is both opportunistic and challenging. By using the concept of pragmatic equidistance and space diplomacy, this paper discusses the situation of Indonesia's space diplomatic relations amidst the three primary spacefaring nations. This paper concludes that Indonesia naturally keeps its distance and tries to take advantage of these conditions, but has not yet systematically and actively used a comprehensive strategy to deal with all three for its own national space interests and agenda.